The Face of Battle: The ‘Fighting First’s’ Baptism of Fire at the Battle of Elandslaagte, 21 October 1899 (Historia, 2023)
This article investigates the experiences of the 1st Battalion of the Manchester Regiment in the Battle of Elandslaagte fought on 21 October 1899 during the South African War of 1899 to 1902. This was the Manchesters’ first battle in nearly two decades and their first against modern weapons. Studies of the experiences of ordinary British soldiers during the South African War are limited. This scrutiny of letters written by the officers and troops of the Manchesters is supplemented by accounts published in British newspapers and an unpublished letter preserved in the Manchester Regiment Archive, all of which have been used to enhance existing narratives of the battle by exploring the soldiers’ perspectives of war. The article suggests that by making use of such sources it is possible to reconstruct the British ‘face of battle’ during the South African War. These published letters have some limitations, however, and are inclined to adhere to the popular ‘Tommy Atkins’ stereotype. Exploring the battle from the Manchesters’ viewpoint reveals that even though Elandslaagte was a near perfect execution of the three-stage set-piece battle, the soldiers involved experienced a turmoil of emotions ranging from confusion, frustration, loss, pain, discomfort, and even joy.
Keywords: Battle of Elandslaagte; the face of battle; experience of battle/combat; New Military History; South African War/Anglo-Boer War; military correspondence in the press; 1st Manchester Regiment